ANALISA CRITICAL PATH METHOD (CPM ) PADA PROYEK PEMBANGUNAN CEKDAM PAKET 2 – KOTA PADANG - Taufik Kurnaini; Helny Lalan; M Adli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Time control is part of project management which also plays an important role in the quality of the implementation of a job. But in reality perfect implementation is very difficult to realize. Sometimes in project implementation there is often a delay in project completion time which results in swelling of project implementation costs. So that the biggest loss and problem is the termination of the contract. It takes a method in project control. Critical Path Method (CPM) can be used in controlling project execution time to minimize deviations in project implementation. The objectives of this thesis include: 1). To know the critical path of work and to calculate the length of time for project implementation using the CPM (Critical Path Method). The results of the analysis there are several activities that are in the critical path. From the results of calculations and rescheduling, the total duration is 165 days, while the duration of the contract 195 days. The activity is completed 30 days earlier.Keywords: Project Management, Cost, Time, Critical Path Method.